Towards More Equitable Land Governance in Vanuatu : Ensuring Fair Land Dealings for Customary Groups - Stefanova, Milena; Porter, Raewyn; Nixon, Rod (World Bank, Washington, DC, 2012)
The regionally unique constitution of the Republic of Vanuatu provides that-all land in Vanuatu belongs to custom owners and their descendants and that the-rule of custom shall form the basis of ownership and use of land. Implementing this principle, however, after decades of land alienation by foreigners using alien laws has proven to be challenging. Concerns over actual and perceived problems of land alienation through leasing in Vanuatu triggered a national land summit in 2006, followed by an interim transitional implementation strategy and a national land review, all of which set the stage for a legislative and administrative reform agenda and served as a guide to short-and long-term assistance to the land sector. This note summarizes the research findings, prioritizes problematic issues for policy consideration, and offers practical for addressing these issues to ensure more equitable and therefore durable future lease creation and lease administration procedures. This study provides an estimate of how much of Vanuatu's land is currently under lease, where land has been leased and how it is being used, the duration of leases, and the extent of lease subdivisions as of December 2010.